Cognitive decline limits compensatory resource allocation within the aged swallowing network - Sonja Suntrup-Krueger; Paul Muhle; Janna Slavik; Jonas von Itter; Andreas Wollbrink; Rainer Wirth; Tobias Warnecke; Rainer Dziewas; Joachim Gross; Sven G. Meuth; Bendix Labeit (GeroScience, 2025)
Cognitive decline has been postulated to predispose to presbyphagia but the neurophysiological basis of this interaction is unclear. To investigate the role of cognition for compensatory resource allocation within the swallowing network and behavioral swallowing performance in dual-task cognitive and motor interference in ageing, volunteers ≥ 70 years of age without preexisting diseases causing dysphagia were investigated using Flexible Endoscopic Evaluation of Swallowing (FEES) including a cognitive and motor dual-task paradigm and a Montreal Cognitive Assessment. The neural correlates of swallowing during dual-task were characterized using magnetoencephalography. Results were related to cognitive function. Sixty-three participants (77.7 ± 6.1 years) underwent FEES, of which 40 additionally underwent MEG. Both cognitive and motor dual-tasks interfered with swallowing function resulting in an increase in pharyngeal residue and premature bolus spillage. The extent of swallowing deterioration (“dual-task cost”) was associated with cognitive decline (cognitive dual-task: Spearman’s rho = − 0.39, p = 0.002; motor dual-task: Spearman’s rho = − 0.25, p = 0.046). When challenged with dual-tasking participants with regular cognition showed compensatory stronger and broader brain activation in cortical pre- and supplementary motor planning areas as well as in frontal executive regions within the cortical swallowing network ( p = 0.004) compared to participants with cognitive deficits. They also performed better in the competing cognitive and motor dual-task and showed fewer incorrect responses ( p = 0.028). Oropharyngeal swallowing involves cognitive cortical processing. Cognitive decline seems to limit the capacity for compensatory resource allocation within the swallowing network. This may lead to deterioration in both swallowing function and concurrent cognitive-motor performance in challenging dual-task situations.